Molecular Insight and Antioxidative Therapeutic Potentials of Plant-Derived Compounds in Breast Cancer Treatment - Sandhya Shukla; Arvind Kumar Shukla; Adarsha Mahendra Upadhyay; Navin Ray; Fowzul Islam Fahad; Arulkumar Nagappan; Sayan Deb Dutta; Raj Kumar Mongre (Onco)
Breast cancer is one of the most common and difficult-to-treat cancers affecting women globally. Long-term treatment success is still limited by problems like drug resistance, toxicity, and recurrence, even with advancements in conventional therapies. The application of substances derived from plants for medical purposes, or phytotherapy, has become a viable adjunctive approach to the treatment of breast cancer. An integrative approach to phytotherapy is examined in this review, focusing on how it can alter important molecular pathways implicated in the development, progression, and metastasis of breast cancer. By focusing on important signaling cascades like TGF-β, Wnt, Hedgehog, Notch, IL-6, Integrins, VEGF, HER2, EGFR, PI3K/Akt, and MAPK, and estrogen receptor pathways, a variety of phytochemicals, such as flavonoids, alkaloids, terpenoids, and polyphenols, demonstrate strong anticancer effects. This review also discusses how they affect immune modulation, angiogenesis, cell cycle regulation, and apoptosis. Moreover, it also emphasizes the challenges with these natural compounds’ bioavailability, standardization, and clinical translation while highlighting preclinical and clinical research that supports their therapeutic potential. This review attempts to give a thorough grasp of how plant-based compounds can support efficient and focused breast cancer treatments by fusing molecular insights with phytotherapeutic approaches.